Viroids in Gummy Bark Sources from the Sultanate of Oman - Bernad, Lucia; Moreno, Pedro; Bove, J. M.; Durán-Vila, Núria (IOCV, 2021)
The gummy bark disease affects sweet oranges and rough lemon in some Mediterranean countries and most countries of the Near and Middle East regions. Diseased trees are usually stunted, and scraping the bark reveals gum deposits. Symptoms of gummy bark in sweet orange resemble those of cachexia on mandarin but the cachexia agent fails to induce symptoms in sweet orange. The causal agent of gummy bark is suspected to be a viroid, but previous studies conducted with sources from Turkey failed to identify a sequence variant of HSVd as the putative disease agent. In the present study, samples collected from Baladi, Valencia, Washington navel and Succari sweet orange trees showing the characteristic gummy bark symptoms were graftinoculated on Etrog citron and analyzed by sPAGE and slot-blot hybridization using viroid-specific probes. In addition to HSVd, all samples also contained CEVd, CVd-III and CVd-IV. Sequence analysis of DNA amplicons generated by RT-PCR using specific primers for these viroids identified novel variants of CEVd (CEVd-gb) and CVd-III (CVd-III-gb) in all the gummy sources, whereas CVd-IV was identical to previously reported sequences. The relationship of these viroids to the putative agent(s) of gummy bark is discussed.